2007
DOI: 10.1590/s1517-83822007000300009
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of the cyclo-oxygenase-inhibitor sulindac sulfide in the filamentous fungus Aspergillus nidulans

Abstract: Sulindac sulfide is a non-steroidal anti-inflammatory drug (NSAID) with chemopreventive effect on human cancer cells. Due to the involvement of the somatic recombination in the carcinogenic process, sulindac sulfide's recombinogenic potential was evaluated by the Homozygotization Index (HI) in the filamentous fungus Aspergillus nidulans. The drug's recombinogenic potential was evaluated by its capacity to induce homozygosis of recessive genes from heterozygous diploid cells. Sulindac sulfide at 175 and 350 µM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…An antiulcerogenic agent, ranitidine, leads to hepatic DNA fragmentation in rodents, probably related to an intragastric nitrosation effect (Brambilla et al, 1983). A non-steroidal anti-inflammatory drug, sulindac, causes DNA breaks and cell cycle anomalies in Aspergillus nidulans (Franco et al, 2007), while three AINE drugs (etodolac, nimesulide and naproxen) elevate the level of SCE in dental patients (Köseoǧlu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An antiulcerogenic agent, ranitidine, leads to hepatic DNA fragmentation in rodents, probably related to an intragastric nitrosation effect (Brambilla et al, 1983). A non-steroidal anti-inflammatory drug, sulindac, causes DNA breaks and cell cycle anomalies in Aspergillus nidulans (Franco et al, 2007), while three AINE drugs (etodolac, nimesulide and naproxen) elevate the level of SCE in dental patients (Köseoǧlu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The children of women who took NSAIDs during the first trimester of pregnancy have presented a greater risk of suffering congenital anomalies such as musculoskeletal deformities (Ofori et al, 2006), cardiac defects and orofacial clefts (Ericson and Källén, 2001). Similarly, some in vivo and in vitro assays have shown that genotoxicity can be generated by various NSAIDs, including paracetamol (Hongslo et al, 1988), sulindac (Franco et al, 2007), ketorolac (Galar et al, 2016) and ibuprofen (Tripathi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of prostaglandin production is not the only mechanism of NSAIDs in fungal cells. Other mechanisms recorded include either cell cycle delay as observed in A. nidulans 4 or inhibition of the function of fungal pathogenic substances such as that of metalloproteinases by diclofenac and piroxicam 36 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cultivation of Trichoderma viride on media containing acetylsalicylic acid (aspirin) or diclofenac revealed strong and dose‐dependent inhibition of the growth of colonies 3 . Exposure of Aspergillus nidulans to 350 μmol l −1 of sulindac sulphide, which is used as a prophylactic agent in colon cancer, showed significant decrease in fungal growth 4 . Herman and Herman [5] demonstrated that aspirin and indomethacin inhibited growth and induced morphological changes of three species of fungi related to the family Saprolegniaceae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation